2016
DOI: 10.1002/bjs.10099
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score-matched outcomes analysis of the liver-first approach for synchronous colorectal liver metastases

Abstract: Patients with sCRLM selected for a liver-first approach had more oncologically advanced disease and a poorer prognosis. They had inferior cumulative DFS than those undergoing a classical approach, a difference negated by matching preoperative BPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 30 publications
5
34
5
Order By: Relevance
“…A clear superiority of this concept has not yet been established, however, a study by Brouquet et al revealed that patients in the liver‐first group had more extensive disease and needed more complex procedures than patients with simultaneous or primary‐first surgery. This assumption was confirmed by a propensity score‐matched analysis in which differences in survival disappeared after matching for a predictive index taking the extent of disease into account . This is a strong indication that patients with more extensive disease benefit from the liver‐first approach.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A clear superiority of this concept has not yet been established, however, a study by Brouquet et al revealed that patients in the liver‐first group had more extensive disease and needed more complex procedures than patients with simultaneous or primary‐first surgery. This assumption was confirmed by a propensity score‐matched analysis in which differences in survival disappeared after matching for a predictive index taking the extent of disease into account . This is a strong indication that patients with more extensive disease benefit from the liver‐first approach.…”
Section: Discussionmentioning
confidence: 72%
“…Another challenge represents the need for a mutual understanding of the disciplines involved in treatment of CRC with synchronous metastases. Potentials, risks, and limitations of each form of the considered treatment must be evaluated to achieve the best results for the patients . Especially the expertise of colorectal, hepatobiliary, thoracic, and peritoneal surface surgeons next to medical and radiation oncologists, interventional radiologists, gastroenterologists, and pathologists should be available within the MDT .…”
Section: Discussionmentioning
confidence: 99%
“…Increased recognition of chemotherapy‐associated postoperative morbidity has led to increased utilization of “liver‐first” approaches in select patients . In most reported series, patients first receive chemotherapy (or radiation in the case of rectal cancer), followed by liver resection, followed by further chemotherapy or colorectal resection depending on the primary tumor . The approach is theoretically appealing in the context of initially unresectable or borderline metastases (numerous/large metastases or questionable liver remnant) requiring conversion chemotherapy and/or staged hepatectomy approaches with asymptomatic primary tumors.…”
Section: Treatment Sequencementioning
confidence: 99%
“…80 In most reported series, patients first receive chemotherapy (or radiation in the case of rectal cancer), followed by liver resection, followed by further chemotherapy or colorectal resection depending on the primary tumor. [81][82][83] The approach is theoretically appealing in the context of initially unresectable or borderline metastases (numerous/large metastases or questionable liver remnant) requiring conversion chemotherapy and/or staged hepatectomy approaches with asymptomatic primary tumors. It is also appealing for patients with simultaneous liver metastases from asymptomatic locally advanced rectal cancer in whom primary tumor downstaging or organ preservation is desirable, 84 When and how to include radiation treatment for the rectal primary tumor is of particular importance in the liver-first approach and highlights the importance of multidisciplinary planning for patients with simultaneous metastases.…”
Section: Liver-first Approachmentioning
confidence: 99%
See 1 more Smart Citation